2000
DOI: 10.1002/1521-4141(200010)30:10<2881::aid-immu2881>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunogenicity of aldehyde-bearing antigens: a possible link between innate and adaptive immunity

Abstract: Innate immunity directs the adaptive immune response by identifying antigens that are associated with infectious agents. Although some microbial antigens can be recognized by innate immune receptors, most cannot, and these require identification by some other means. The introduction of aldehydes into antigens by glycolaldehyde, which can be produced by activated neutrophils reacting with serine, or by the oxidation of an N‐linked oligosaccharide with NaIO4, enhances by several orders of magnitude their immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…This reaction has been extensively used to attach molecules to carrier proteins, to degly-cosylate glycoproteins, and also to stabilize protein structures [19][20][21][22]. In addition, it has been demonstrated that the introduction of aldehydes into OVA by the oxidation of their oligo-saccharides with sodium periodate enhances their immunogenicity [23].…”
Section: Introductionmentioning
confidence: 64%
“…This reaction has been extensively used to attach molecules to carrier proteins, to degly-cosylate glycoproteins, and also to stabilize protein structures [19][20][21][22]. In addition, it has been demonstrated that the introduction of aldehydes into OVA by the oxidation of their oligo-saccharides with sodium periodate enhances their immunogenicity [23].…”
Section: Introductionmentioning
confidence: 64%
“…Our previous experiments showed that oxidation of SK-OV-3 cells with 60 Amol/L HOCl induced >99% tumor cell death (14). Dendritic cells (2 Â 10 6 ) were therefore pulsed with 2 Â 10 6 60 Amol/L HOCl-oxidized SK-OV-3 cells (prepared as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the Schiff base-forming agent tucaresol, in addition, during immunization with protein antigen increased T cell dependent immune response. Direct modification of protein antigen has been shown to be required for the enhancement of the immune response [6,[9][10][11][12].…”
Section: Oxidation and Immune Responsementioning
confidence: 99%